Navigating the E-commerce Labor Nexus: Trends, Challenges, and Socio-Economic Implications - Safitri, Sifa' Ulya; Mediawati, Noor Fatimah; Hasan, Rizqi (Proceedings of The ICECRS, 2023)
This data article presents findings from an examination of 12,662 journal articles and conference proceedings obtained by searching Lens.org using the keywords "e-commerce AND Labor." The objective was to gauge the quantity of journal articles at the intersection of e-commerce and labor within Online Business Law. Serving as a valuable resource, this dataset offers researchers and authors a platform for gaining insights, conducting literature reviews, and shaping future experiments in this field. Highlights : Analysis of 12,662 documents at the intersection of e-commerce and labor. Valuable resource aiding insights, literature reviews, and future experimentation. Focused on the nexus between e-commerce and labor within Online Business Law. Keywords: E-commerce, Labor, Online Business Law, Journal Articles, Conference Proceedings